STUDY OF GOOD CORPORATE GOVERNANCE IMPLEMENTATION IN LISTED STATE-OWNED ENTERPRISES THROUGH A CONTENT ANALYSIS METHOD OF ANNUAL REPORTS - Sally Marcelina Djauhari; Raymondus Parulian Sihotang (Journal of Applied Finance & Accounting, 2010)
Good Corporate Governance (GCG) is a concept of directing and controlling business corporations. This concept specifies the distribution of rights and obligations between the company’s stakeholders and the procedures for taking decisions on corporate affairs. It provides a mechanism through which the company’s objectives are set, and for attaining those objectives and monitoring performance. The main objective of this study is to explore how far the GCG principles have been implemented in listed State-Owned Enterprises (SOE). In addition, the writer compares the GCG implementation among the participant companies as well as across the industries, in which the companies are classified. The method used in the data collection is observation through the company’s annual report (content analysis). The writer uses GCG Evaluation Manual of Badan Pengawasan Keuangan dan Pembangunan (BPKP) released and endorsed in 2004 by the Ministry of SOE, as the scoring system. The results generated from this study are the company’s scores in implementing the GCG principles. In addition, the writer generates ranking among the participant companies, within the same industry and across the industries. The best company with the highest score in implementing the GCG principles among the participant companies is Aneka Tambang. In addition, the top companies with the highest scores within each industry are Bank BNI (Finance), Indofarma (Consumption Goods), Telkom (Infrastructure, Utility & Transportation), and Aneka Tambang (Mining). Moreover, the best industry with the highest average score of the players is Property & Real Estate.